FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN KONTROL KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Aryatika, Karera; Amin, Hadriyani; Wirawan, Susilo; Azuma, Anindita Paramastuti; Pramono, Yosra Sigit (Ensiklopedia of Journal, 2024)
Abstract: Based on data obtained by Puskesmas Simpang IV Sipin, the number of patients with diabetes mellitus is striking. In 2022, this health center recorded 295 patients with diabetes mellitus. However, in 2023, the number increased rapidly to 91 people. The purpose of the study was to determine the factors associated with compliance with blood sugar control in patients with type 2 diabetes mellitus. The study used a type of quantitative research with a cross sectional design. The research was conducted in October 2023 at Puskesmas Simpang IV Sipin. The sample amounted to 73 people. The sampling technique used Accidental Sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed there was a relationship between family support (p value: 0.001) and there was no relationship between motivation (p value: 0.716) with compliance with blood sugar control in patients with type 2 diabetes. It is recommended for families and health workers to be able to maintain and continue to increase support for patients with type 2 DM to always be obedient to control blood sugar levels such as reminding to control blood sugar levels in addition to preventing complications.Keywords: Diabetes, Family Support, Motivation.